2016
DOI: 10.1126/sciadv.1501297
|View full text |Cite
|
Sign up to set email alerts
|

Shape memory polymer network with thermally distinct elasticity and plasticity

Abstract: Shape memory polymer with thermally distinct elasticity and plasticity enables highly complex shape manipulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
421
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 457 publications
(429 citation statements)
references
References 34 publications
7
421
0
1
Order By: Relevance
“…This rapid fabrication of shape memory polymers with complex 3D permanent geometries is highly desirable for device applications of shape memory polymers. [1,6,30] In particular, the low surface energy of the wax-like material along with its shape memory function makes it highly attractive for use as smart molds to make polymer parts. In addition, the material can also be used for lost-wax casting, in which the wax-based material serves as the sacrificial mold (burned out after the process) to make metal parts with intricate 3D shapes (e.g., custom jewelry).…”
Section: Doi: 101002/adma201605390mentioning
confidence: 99%
“…This rapid fabrication of shape memory polymers with complex 3D permanent geometries is highly desirable for device applications of shape memory polymers. [1,6,30] In particular, the low surface energy of the wax-like material along with its shape memory function makes it highly attractive for use as smart molds to make polymer parts. In addition, the material can also be used for lost-wax casting, in which the wax-based material serves as the sacrificial mold (burned out after the process) to make metal parts with intricate 3D shapes (e.g., custom jewelry).…”
Section: Doi: 101002/adma201605390mentioning
confidence: 99%
“…The urethane coatings were reported to undergo hydrolysis in the body, resulting in the presence of aromatic amines formed after hydrolysis of the carbamate, but the hydrolysis was a result of testing conditions that did not align with what the material would have experienced in vivo . This ultimately yielded data that does not accurately predict toxicity and stability over time [1–3,17–21]. Additional long term studies of these polyurethane foams have further indicated a reduced rate of tumorogenesis, no association between cancer incidence and the use of the aromatic diisocyanates, and no long term risk of cancer in both animal and human studies.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Photons with frequencies lying in the PBGs cannot propagate through the crystals, providing enormous opportunities in controlling the flow of light in miniature volumes for photo nic information technology, such as nextgeneration all-optical integrated circuits. [12][13][14][15][16][17] Smart shape memory polymers (SMPs), which can memorize and transit between a permanent shape and one or multiple temporary configurations in responding to various stimuli, such as heat, light, solvents, and electromagnetic fields, [18][19][20][21][22][23][24][25] may hold the key to truly reconfigurable photonic crystals. [12][13][14][15][16][17] Smart shape memory polymers (SMPs), which can memorize and transit between a permanent shape and one or multiple temporary configurations in responding to various stimuli, such as heat, light, solvents, and electromagnetic fields, [18][19][20][21][22][23][24][25] may hold the key to truly reconfigurable photonic crystals.…”
Section: Introductionmentioning
confidence: 99%